2017
DOI: 10.1007/s40136-017-0144-6
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Engineered Larynx: Future Applications in Laryngeal Cancer

Abstract: Purpose of ReviewThis article reviews the latest developments in tissue engineering for the larynx with a specific focus on the treatment of laryngeal cancer.Recent FindingsChallenges in tissue engineering a total larynx can be divided into scaffold design, methods of re-mucosalization, and how to restore laryngeal function. The literature described a range of methods to deliver a laryngeal scaffold including examples of synthetic, biomimetic, and biological scaffolds. Methods to regenerate laryngeal mucosa ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 70 publications
0
15
0
2
Order By: Relevance
“…Standard treatments for advanced cancer, which involve surgical resection and/or chemoradiation, are life‐saving but may render patients dependent on a tracheostomy and/or feeding tube with poor quality of life. A recent review by Hamilton and Birchall indicated that one treatment strategy for advanced laryngeal cancer is to tissue engineer a functional laryngeal replacement . This, they postulate, can be broken down into a number of design considerations, including restoration of 1) structure through scaffold design and 2) function by promoting skeletal muscle regeneration with associated vascularization and innervation.…”
Section: Introductionmentioning
confidence: 99%
“…Standard treatments for advanced cancer, which involve surgical resection and/or chemoradiation, are life‐saving but may render patients dependent on a tracheostomy and/or feeding tube with poor quality of life. A recent review by Hamilton and Birchall indicated that one treatment strategy for advanced laryngeal cancer is to tissue engineer a functional laryngeal replacement . This, they postulate, can be broken down into a number of design considerations, including restoration of 1) structure through scaffold design and 2) function by promoting skeletal muscle regeneration with associated vascularization and innervation.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the restoration of laryngeal function after partial or total laryngectomy is only partly possible and is associated with major impairment for the patients. Hamilton and Birchall state in a recent review article that the treatment of laryngeal cancer will be crucially influenced by the developments in the field of laryngeal regeneration over the next 10 years 92 . Larynx transplantation is currently mainly a theoretical option that can only be applied in exceptional cases and that is not suitable for reconstruction after tumor surgery.…”
Section: Regenerative Procedures In Otorhinolaryngology – State-ofmentioning
confidence: 99%
“…27 The concept of transplanting a biocompatible cartilage scaffold covered in the patient's own epithelium, which integrates with the host tissue thereby negating the rejection process, would revolutionize the treatment of laryngeal cancer and improve the prospect of organ and functional preservation. 28 There are multiple challenges which exist, however, before this concept can be transferred into clinical practice, and this may take at least another 10 years to see fruition.…”
Section: Tissue-engineered Larynxmentioning
confidence: 99%